Influence of preoperative hospital stay in the antimicrobial resistance profile of oral microbiotic - Campêlo, Clarissa Sales de Paula; Silva, Paulo Goberlânio de Barros; de Carvalho, Bráulio Matias; Sampaio, Eliane Ferreira; Nottingham, Tatiane Andrade Figueiredo Rojas; de Souza, Pedro de Freitas Santos Manzi; Alves Filho, André Luis Almeida; Sousa, Fabrício Bitu; Bandeira, Tereza de Jesus Pinheiro Gomes (Journal of Health & Biological Sciences, 2021)
Objective: Verify whether there was a relationship between the occurrence of multidrug-resistant bacterial strains and the length of stay in the preoperative period. Methods: Clinical samples of the oral surfaces of the teeth and/or cheek mucosa were collected in the oral cavity of 37 patients who underwent elective cardiac surgery in the preoperative period from May to July 2019. The clinical samples collected were subjected to identification of colonies and antimicrobial sensitivity tests. Results: We observed that the patients who stayed for more than 60 days in that hospital had 17 times more likely to develop multi-resistant strains (Multi-Rs) than those that have not remained. Conclusions: We realized that the longer the patient stays in the hospital, the greater the chances of bacterial strains Multi-Rs. Therefore, it is important to try to reduce the length of hospital stay so that there is no increase in the occurrence of multiresistant strains in these patients